2019
DOI: 10.1111/aos.14067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of selective laser trabeculoplasty as an intraocular pressure lowering option

Abstract: Purpose Selective laser trabeculoplasty (SLT) is one of the many treatment options for lowering intraocular pressure (IOP) in patients with glaucoma. This study aimed to evaluate the effect of SLT. Methods Data were collected from medical records of 289 patients who underwent SLT treatment (180° of trabecular meshwork) during 2014 and 2015 at the Department of Ophthalmology, Sahlgrenska University Hospital, Mölndal, Sweden. Baseline characteristics and information from a follow‐up within 100 days were also rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Some of the previously published work excluded patients with advanced visual field defects, systemic steroid use, and previous eye surgeries. [2,3,8] No such exclusions were made in this study, which could contribute to the observed disparity in the success rates of SLT.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Some of the previously published work excluded patients with advanced visual field defects, systemic steroid use, and previous eye surgeries. [2,3,8] No such exclusions were made in this study, which could contribute to the observed disparity in the success rates of SLT.…”
Section: Discussionmentioning
confidence: 96%
“…It is generally regarded as effective and safe. Prior studies have indicated that the IOP-reducing ability of SLT is comparable to that of topical glaucoma drops [2][3][4]. However, SLT may be preferred over topical drops as it potentially avoids any associated side effects as well as issues that may arise from variable patient adherence [1,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, medication currently serves as the mainstream first-line treatment for POAG and OHT 14 . Studies in China 15,16 and other countries [17][18][19] have reported greatly varied treatment efficacy for SLT which is possibly due to differences in severity of glaucoma, ethnic background 20,21 , laser energy used, treatment area and length of follow-up. In the past, SLT has been mainly used for cases with uncontrolled IOP, intolerance to medical therapy and poor compliance in mild POAG [46][47][48] .…”
Section: Introductionmentioning
confidence: 99%
“…Where efficacy is concerned, most SLT studies have reported a high success rate of~6.9-35.9% reduction in IOP for OAG [10]. However, the predictability of SLT has been reported to be variable in some studies [11], with this inconsistency attributed to factors such as the patient population, type of glaucoma, SLT treatment protocol, or even surgeon factors-with failure rates of up to 60% reported in certain studies [12]. Furthermore, the effect of laser trabeculoplasty has been reported to decrease over time [13], with 68% of eyes in the GLT requiring additional IOP-lowering interventions after 5 years.…”
mentioning
confidence: 99%